Dynamics and distribution of Jovian dust ejected from the Galilean satellites. Issue 7 (5th July 2016) - Liu, Xiaodong; Sachse, Manuel; Spahn, Frank; Schmidt, Jürgen
Abstract: In this paper, the dynamical analysis of the Jovian dust originating from the four Galilean moons is presented. High‐accuracy orbital integrations of dust particles are used to determine their dynamical evolution. A variety of forces are taken into account, including the Lorentz force, solar radiation pressure, Poynting‐Robertson drag, solar gravity, the satellites' gravity, plasma drag, and gravitational effects due to nonsphericity of Jupiter. More than 20, 000 dust particles from each source moon in the size range from 0.05 μm to 1 cm are simulated over 8000 (Earth) years until each dust grain hits a sink (moons, Jupiter, or escape from the system). Configurations of dust number density in the Jovicentric equatorial inertial frame are calculated and shown. In a Jovicentric frame rotating with the Sun the dust distributions are found to be asymmetric. For certain small particle sizes, the dust population is displaced towards the Sun, while for certain larger sizes, the dust population is displaced away from the Sun. The average lifetime as a function of particle size for ejecta from each source moon is derived, and two sharp jumps in the average lifetime are analyzed. Transport of dust between the Galilean moons and to Jupiter is investigated. Most of the orbits for dust particles from Galilean moons are prograde, while, surprisingly, a small fraction of orbits are found to become retrograde mainly due to solar radiation pressure and Lorentz force. The distribution of orbital elements is also analyzed. Key Points: Simulations of micron‐sized particles ejected from the four Galilean moons are carried out Using forces and sinks relevant for small particles, their distribution in the system is obtained Size‐dependent particle lifetimes are determined, and a population of retrograde grains is found